Privacy, intrusion detection, and response : technologies for protecting networks - Kabiri, Peyman , 1968- (Information Science Reference, 2012)
"This book discusses the latest trends and developments in network security and privacy, and serves as a vital reference for researchers, academics, and practitioners working in the field of privacy, intrusion detection, and response"--Provided by publisher